The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
https://uqam-bib.on.worldcat.org/oclc/953804743
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Routledge handbook of sexuality, health and rights - Aggleton, Peter; Parker, Richard Guy (Routledge, 2010)
This handbook surveys the state of the discipline, including examination and discussion of emerging, controversial and cutting edge areas. It is an essential reference for all academics and researchers in the fields of sexuality studies, sexual health and human rights, as well as very useful reading for more advanced students.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; droits; outils; ouvrages de références; périodes historiques; santé; santé reproductive; sexualité; thématiques

Les Panthères roses de Montréal : un collectif queer d'actions directes. - Collectif de recherche sur l'autonomie collective (Collectif de recherche sur l'autonomie collective., 2010)
Cette monographie a été réalisée sur le mode de la recherche-action. Cette approche méthodologique suppose que les membres du collectif recensé participent activement à la production de connaissances sur leur groupe, sur leur mode d’organisation. Ce faisant, on espère que la réflexion qui s’en dégage participe aussi de la dynamique d’émancipation, d’appropriation et de partage des savoirs et des savoir-faire. On suppose donc qu’un projet vraiment émancipateur implique les actrices et acteurs du début à la fin : de la conceptualisation, à la réalisation et, finalement, à la diffusion des résultats. Concrètement, en tant que membre du CRAC-K, Julie Grolleau a approché les membres des Panthères roses à l’automne 2006. Les entrevues individuelles ont pu commencer. Sur la base des éléments dégagés de ces entrevues, un entretien collectif de retour et d’approfondissement a été effectué. Ce matériau a été analysé en suivant la codification du CRAC-K sur les questions concernant l’autonomie collective et en tenant compte des textes diffusés sur le site des Panthères roses (communiqués d’action, images, textes). Une première version de la monographie a été soumise aux membres du groupe, afin de s’assurer qu’illes s’y reconnaissent et soient en accord avec son contenu. Une seconde version mise en page leur a enfin été envoyée et c’était la fin d’un long et stimulant processus.
https://numerique.banq.qc.ca/patrimoine/details/52327/2163531
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; fem1000; outils; pratiques féministes; premier cycle; périodes historiques; queer; québec; recherche en milieux de pratique; recherche partenariale; recherche-action; ressource en ligne; régions géographiques; soc2014